Finding new objectives, seeking new instruments - David Cobham (Heriot-Watt University, Department of Accountancy, Economics, and Finance, 2024)
This short paper use the perspective of the assignment problem to examine the evolution of the workings of monetary policy and the Monetary Policy Committee (MPC) of the Bank of England over its first 25 years. It outlines how the Bank, and the MPC, came across additional possible objectives and searched for additional possible instruments. It then argues the need for some recasting of the role of the MPC and the way in which it operates.
Keywords: E42; E52; E58; F33; 330; assignment problem; monetary policy; inflation targeting; inflation; economic growth